Fiscal Policies for Gender Equality - Gabriela Rigoni; José A. Stracquadaini (PT Penjaminan Infrastruktur Indonesia (Persero), 2022)
Preventing economic distortions and providing for gender equality should be a main goal that could be achieved not only by promoting labor laws and ensuring welfare benefits, but also with the design of a tax-benefits system that could address those issues. A gender-sensitive tax-benefits system would become a permanent safeguard policy for gender issues, promoting gender inclusion.